Direct-to-chip liquid cooling for reducing power consumption in a subarctic supercomputer centre. (2016) - Ovaska, Seppo J.; Dragseth, Roy E.; Hanssen, Svenn A.
Reduction of data centre power consumption is a timely challenge. Waste heat reuse is another focus area when developing energy efficient and sustainable data centres. And these two issues are interconnected through liquid cooling of server racks and/or direct-to-chip liquid cooling. Both of these solutions make it possible to transfer a significant proportion of the waste heat energy back to profitable use. Nevertheless, the heat reusing opportunity is not the only benefit direct-to-chip liquid cooling may offer. Another benefit is the notable reduction of power consumption related to cooling fans associated with server blades and rack-level cooling systems. To evaluate this benefit, we performed power consumption and performance measurements in a subarctic supercomputer centre hosting a cluster of 632 blade nodes. Our study concentrated on a 47-node subset that we analysed when the servers were executing the LINPACK benchmark. Our conclusion is that direct-to-chip liquid cooling can reduce the total power consumption, in this case, up to 14.4% depending on the inlet air temperature.